New magnetic flux flows with Heisenberg ferromagnetic spin of optical quasi velocity magnetic flows with flux density - Korpinar, T.; Demirkol, R. Cem; Korpinar, Z.; Asil, V (Soc Mexicana Fisica, 2021)
In this article, we first offer the approach of quasi magnetic Lorentz flux of quasi velocity magnetic flows of particles by the quasi frame in 3D space. We then obtain new optical conditions of quasi magnetic Lorentz flux by using directional quasi fields. Moreover, we determine the quasi magnetic Lorentz flux for quasi vector fields. Additionally, we give new constructions for quasi curvatures of quasi velocity magnetic flows by considering Heisenberg ferromagnetic spin. Finally, the magnetic flux surface is demonstrated on a static and uniform magnetic surface by using the analytical and numerical results.
Keywords: Quasi directional frame; flows; Heisenberg ferromagnetic spin; geometric magnetic flux density